Pengaruh Earnings Per Share (EPS) dan Price Terhadap Book Value (PBV) tentang Harga Saham Perbankan Syariah dan Konvensional di BEI (2020-2022) - Sofhian Sofhian; Roni Mohamad; Zulkifli Repikasa Asipu (Al-Buhuts, 2024)
This study aims to determine: (1) Does Earning Per Share affect the stock price of Islamic banking. (2) Does Earning Per Share affect the stock price of conventional banking. (3) Does Price to Book Value affect the share price of Islamic banking. (4) Does Price to Book Value affect the share price of Conventional banking. (5) Do Earning Per Share and Price to Book Value affect the share price of Islamic banking. (6) Do Earning Per Share and Price to Book Value affect the stock price of Conventional banking. The population in this study were Islamic and conventional banking companies listed on the Indonesia Stock Exchange with samples taken, with samples selected 3 Islamic banking companies and 3 conventional banks. Sampling using purposive sampling method. The results of this study indicate that the effect of EPS and PBV on the share price of Islamic and conventional banking shows a significant difference. Overall, the value of EPS and PBV of conventional banking is superior to the value of EPS and PBV of Islamic banking. However, the value of EPS and PBV of Islamic banking tends to be stable and able to grow positively